2016
DOI: 10.1186/s13561-016-0128-0
|View full text |Cite
|
Sign up to set email alerts
|

Design and implementation of community engagement interventions towards healthcare quality improvement in Ghana: a methodological approach

Abstract: BackgroundNearly four decades after the Alma-Ata declaration of 1978 on the need for active client/community participation in healthcare, not much has been achieved in this regard particularly in resource constrained countries like Ghana, where over 70 % of communities in rural areas access basic healthcare from primary health facilities. Systematic Community Engagement (SCE) in healthcare quality assessment remains a grey area in many health systems in Africa, albeit the increasing importance in promoting uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(47 citation statements)
references
References 23 publications
1
46
0
Order By: Relevance
“…This was a cluster randomised trial in 64 primary health facilities (32 intervention and 32 control) and their catchment area, as detailed in previous related publications by the lead author [58]. Primary health facilities in this context are clinics and health centres as per the Ghana Health Service (GHS) categorizations and pyramidal levels of healthcare.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This was a cluster randomised trial in 64 primary health facilities (32 intervention and 32 control) and their catchment area, as detailed in previous related publications by the lead author [58]. Primary health facilities in this context are clinics and health centres as per the Ghana Health Service (GHS) categorizations and pyramidal levels of healthcare.…”
Section: Methodsmentioning
confidence: 99%
“…This study setting and population are the same as previous publications by the lead author using the same research design and approach (see Alhassan et al [58]). The study was thus conducted in the Greater Accra and Western regions of Ghana in 16 administrative districts.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…An approach used by Alhassan et al [42] found that facilitating systematic community engagement (SCE) interventions around quality of care enabled existing community groups to reflect on perceived quality of care, using 10 pre-defined domains detailed on a community scorecard. Community feedback was shared with health providers who used the information to develop action plans to address gaps in perception of quality.…”
Section: Discussionmentioning
confidence: 99%